Design, fabrication, and installation of the cryogenic distribution system for FRIB target and fragment pre-separator superconducting magnets. Issue 1 (1st May 2022) - Hasan, N; Wright, M; Ganni, V; Casagrande, F; Jones, S; Nguyen, C; Fila, A; Joseph, N
Abstract: The target and fragment pre-separator segment of the continuous wave heavy ion beam linear accelerator at FRIB consists of fourteen superconducting magnets. The cryogenic distribution system for these superconducting magnets include six cryogenic process pipes (two each for 4.5 K helium, cool-down and thermal shield) housed in an approx. 175 m long vacuum jacketed transfer line, along with associated distribution boxes, cool-down heat exchanger, utility piping (such as magnet lead flow return, purge gas etc.) and a liquid helium storage vessel for magnet quench management. Due to the physical constraints in the routing of the beam-line at this segment, designs for these magnets and the associated cryogenic distribution system are complex in nature. It poses challenges in several aspects of the design process such as, routing of the transfer line, design of piping supports and anchors, thermal shielding, mechanical flexibility etc. Design of most of the elements of the cryogenic distribution system are carried out from the ground up, and in-house at FRIB. This paper presents an overview of the process design, analysis, fabrication and installation the target and fragment pre-separator cryogenic distribution system at FRIB.